COMPARATIVE STUDY OF IN-VITRO TOXICITY OF RAW HONEY AND FERMENTED HONEY USING THE BSLT (BRINE SHRIMP LETHALITY TEST) METHOD - Wulansari, Devyani; dyah wulandari, devyana; Krisdayanti, Affina (TEKNOLOGI MEDIS DAN JURNAL KESEHATAN UMUM, 2022)
Honey is an alternative product used in traditional medicine because of concerns, honey is a sweet liquid made by bees using flower nectar. Raw honey has low water content and high sugar content, when the water content in honey is high it makes honey easy to ferment. The samples used were raw honey and fermented honey. Raw and fermented honey contains phenolic compounds that can act as anticancer candidates by testing anticancer compounds in the form of toxicity measurements using the BSLT method. The honey sample yielded a toxicity of 59.75 μg/mL. While the fermented honey sample obtained an LC50 value of 3.28 μg/mL, which means the LC50 value was 30 ppm, indicating that the fermented honey sample was included in the very toxic category. Toxicity test on raw honey samples showed the LC50 value was in the toxic range. In the toxicity test, the fermented honey sample showed an LC50 value of 30 ppm, which means that the fermented honey has a very toxic toxicity value. There are differences in LC50 values in the second sample. However, statistically, there is no significant difference between raw honey and fermented honey